2020
DOI: 10.1016/j.jsxm.2020.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Evaluation of Functional Nerve Regeneration in Transgender Individuals After Phalloplasty with a Free Radial Forearm Flap

Abstract: Background Constructing a sensitive phallus is a key objective in sex affirmation surgery, but still there is a major lack of evidence in outcome analysis of postoperative sensibility of the newly constructed body part. Aim To evaluate the innervation and sensibility of a forearm free-flap neophallus with nerve coaptation by a broad-spectrum follow-up. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
2
14
0
5
Order By: Relevance
“…Based on these patient-reported outcomes, we have (previous to this study) ceased to connect the medial antebrachial cutaneous nerve in favor of patient comfort. Possible this may also affect the tactile sensitivity outcomes, nevertheless, our patients seem to experience the same level of tactile sensitivity as reported by Selvaggi et al and Kuenzlen et al 12 , 17 …”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Based on these patient-reported outcomes, we have (previous to this study) ceased to connect the medial antebrachial cutaneous nerve in favor of patient comfort. Possible this may also affect the tactile sensitivity outcomes, nevertheless, our patients seem to experience the same level of tactile sensitivity as reported by Selvaggi et al and Kuenzlen et al 12 , 17 …”
Section: Discussionsupporting
confidence: 82%
“…Several previous studies showed that sensory recovery of the neophallus after nerve coaptation is possible for various flap techniques, but the overall tactile sensation recovery remains suboptimal in all presented techniques. 6 , 8 , 10 , 12 , 17 , 18…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations